Internal Control: Fraud Detection and Prevention by Forensic Accounting - Rahman, Md. Mahofuzur (Asian Accounting and Auditing Advancement, 2021)
The word "forensic" originates from the Anglo-Saxon language and originally referred to a criminal service that collected evidence at crime scenes. However, in today's modern world, criminal activity does not just occur "on the road;" it also occurs in commercial traffic. In most cases, it is not immediately clear that the crime scenes and those involved are engaged in commercial transactions. Criminal acts are typically concealed behind contracts, payments, and other types of business transactions. Therefore, the hard skills necessary to deal with a traditional criminal offense stemming from them are skills related to economic crime. In addition to the traditional function of the state, which is to combat crime and is typically carried out by the public prosecutor and the police, a new career path known as forensic accounting has emerged. The purpose of this research is to determine whether or not there is a connection between forensic accounting, forensic consulting, or any of their respective areas of expertise and fraud and fraud auditing. There are many different types of stakeholders who require the services of forensic accountants. These may include attorneys, members of the police and other law enforcement agencies, financial institutions, banks, courts, the business world, government representatives, and legal entities affiliated with the government. Within the context of enterprise financial fraud detection and prevention tools as essential measures of internal control systems, this study investigates those tools.